Gradual ulnar lengthening in children with multiple exostoses and radial head dislocation: results at skeletal maturity - D’Ambrosi, Riccardo (J Child Orthop, 2016)
PURPOSE: Deformities of the forearm and shortening of the ulna occur in 30 % of patients with hereditary multiple exostoses (HME), leading to radial head dislocation and loss of movement. Several surgical techniques have been described for treatment, and the aim of our study was to present clinical and radiographic results at skeletal maturity in 15 children that underwent the surgical procedure of ulnar lengthening with external fixators. METHODS: We evaluated 15 patients with ulnar shortening and radial head dislocation that underwent external fixation procedures. Radiographic assessment included measurement of radial articular angle, carpal slip, and ulnar shortening. Clinical evaluation included range of motion, MAYO Elbow Score, assessment function of the extremity as described by Stanton, the visual analog scale (VAS) for pain, and SF-12 to evaluate quality of life. RESULTS: The average follow-up period was 77 months and took place when each patient had reached skeletal maturity. MAYO Elbow Score improved from 34.7 to 93.3 points, while the average preoperative functional assessment criteria score was 1.6 points and improved to 4.4. The preoperative average VAS ranged from 8.2 to 2.3, while the SF-12 in its physical (PCS) and mental (MCS) components resulted, respectively, as 53.3 and 54.2. Pronation and supination improved from a preoperative average value of 35.6° and 51.3° to 70° and 80.6°, respectively, at the most recent follow-up visit. Flexion and extension ranged, respectively, from 143° and 2° to 146.7° and 3°. Ulnar shortening improved from 24 mm preoperative to 3 mm, and radial articular angle varied from 37.7° preoperative to 26° at the last follow-up. Only one complication occurred in our group, and one patient completely healed from a case of nonunion of the ulna. CONCLUSIONS: Ulnar lengthening is a safe and reliable procedure for the treatment of HME that provides good to excellent results and reduces radial head dislocation.